PERSEPSI PESERTA DIDIK TERHADAP METODE BLENDED LEARNING DENGAN GOOGLE CLASSROOM PADA PESERTA DIDIK KELAS XI DI SMK KRISTEN BM SALATIGA - Anita Irawan (JURNAL CAPITAL : Kebijakan Ekonomi, Manajemen dan Akuntansi, 2021)
Abstract. This study to determine how the students' perceptions of the blended learning method with Google Classroom for the XI grade students of SMK Kristen BM Salatiga. The research was conducted by taking as many as 30 person a sample of teachers and students at SMK KRISTEN BM Salatiga. Sampling of data sources by Questioner was done with purposivesampilng, triangulation validity techniques, inductive / qualitative data analysis.Qualitative research results emphasized meaning rather than generalization. The results of the analysis show that the Principal, Teachers and Students understand and know blended learning using Google Classroom and students in general do not have difficulty understanding and carrying out the blended learning learning process using Google Classroom.Butthe blended learning learning method still has not had a positive impact on students because the learning process still tends to make students less motivated and less independent to learn so that learning outcomes are not good. The facilities and infrastructure in schools are still not optimal to support the blended learning process and some subjects cannot be fully carried out by online learning method.